Language And Ecology: A Semantic Analysis Of Environmental Vocabulary In Indonesian Regional Languages - Lukmanul Hakim; Fadhilah Arfa Hasibuan; Dewi Ismu Purwaningsih; Silva Fitri (Yayasan Adra Karima Hubbi, 2025)
Background. This research explores the intricate relationship between language and the environment by investigating the ecological vocabulary embedded within Indonesian regional languages. The archipelagic nature of Indonesia has fostered immense linguistic and cultural diversity, which includes a sophisticated, locally-grounded understanding of the natural world. However, this traditional ecological knowledge (TEK), encapsulated in unique lexicons, faces erosion due to language shifts and environmental degradation. Purpose. This study aims to conduct a semantic analysis of environmental vocabularies in selected Indonesian regional languages to document and understand the depth of ecological knowledge they contain. Method. Adopting a qualitative approach rooted in ecolinguistics and ethnosemantics, this study collects and analyzes lexical items related to flora, fauna, and natural phenomena. Results. The findings reveal a highly granular and nuanced classification system, reflecting a profound and long-standing interaction between local communities and their specific ecosystems. Conclusion. This research concludes that regional languages are critical reservoirs of ecological wisdom. The preservation of this linguistic diversity is paramount not only for cultural heritage but also for informing contemporary environmental conservation strategies.